Knowledge and Attitude Regarding Polycystic Ovarian Syndrome among Undergraduate Nursing Students of Teaching Hospital Bharatpur, Nepal - Yadav, Namita; Sedain, Prativa (Journal of College of Medical Sciences-Nepal, 2025)
Background Polycystic ovarian syndrome (PCOS) is a hormonal disorder of reproductive age and affects 6 to 22% of women worldwide. A limited study was conducted to explore knowledge and attitude toward PCOS among undergraduate students in Nepal. This research specifically aimed to assess the knowledge and attitudes regarding PCOS among undergraduate nursing students at a teaching hospital in Bharatpur, Nepal. Methods This was a cross-sectional study, conducted among 113 undergraduate nursing students studying at the College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. All eligible undergraduate nursing students at the college were included. Data were collected using a structured questionnaire after obtaining informed consent. The data were analyzed with SPSS version 16 and expressed using descriptive statistics (frequency and percentage). Results The age of the participants ranged from 17 to 23 years, with a mean age of 19.83±1.24. All the participants were unmarried. The majority of participants (98.2%) heard about PCOS. The major sources of knowledge were the internet (72.6%), followed by teachers (17.7%), then other sources such as radio, TV, and newspapers (6.2%), and least from parents (3.5%). Most of the participants had adequate knowledge (61.1%), followed by moderate knowledge (34.5%), and 4.4% had inadequate knowledge about PCOS. Most of the undergraduate nursing students showed a neutral attitude (57.5%), followed by a favorable attitude (46.7%), and the least had an unfavorable attitude (1.8%) towards PCOS. Conclusions This study found that undergraduate nursing students had adequate knowledge and a favorable attitude towards PCOS.